Re‐evaluation of β‐cyclodextrin (E 459) as a food additive. (7th December 2016) - ,; Mortensen, Alicja; Aguilar, Fernando; Crebelli, Riccardo; Di Domenico, Alessandro; Dusemund, Birgit; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Leblanc, Jean‐Charles; Lindtner, Oliver; et al.
Abstract: The EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re‐evaluating the safety of β‐cyclodextrin (E 459) as a food additive. β‐Cyclodextrin is a non‐reducing cyclic oligosaccharide consisting of seven α‐1, 4‐linkedd ‐glucopyranosyl units. The Scientific Committee on Food (SCF) allocated an acceptable daily intake (ADI) of 5 mg/kg body weight (bw) per day to β‐cyclodextrin (E 459) in 1996. β‐Cyclodextrin is poorly absorbed following oral administration in animals and humans. It is hydrolysed to maltose and glucose by the gut microflora and endogenous amylases in the colon; consequently, β‐cyclodextrin levels in tissues and serum are low (< 1%). β‐Cyclodextrin has a low acute oral toxicity. Short‐term and subchronic toxicity studies were available in rats and dogs. In rats, the main reported effect was an adaptive enlargement of the caecum, resulting from consumption of poorly digestible carbohydrates. From a 6‐month study in rats, a no observed adverse effect levels (NOAEL) of 600 mg/kg bw per day was identified and from a 52‐week dogs study, the NOAEL was 466 and 476 mg/kg bw per day in males and females, respectively. The Panel considered that there was no indication for genotoxicity of β‐cyclodextrin. From a chronic toxicity studies in rats, a NOAEL of 654 and 864 mg/kg bw per day in males and females, respectively, was identified. Carcinogenicity studies in mice and rats were available and no evidence for carcinogenicity was found. The Panel concluded that, based on the available toxicological database, there is no reason to revise the current ADI of 5 mg/kg bw per day for β‐cyclodextrin. Based on the available reported use and use levels, the Panel also concluded that the ADI was exceeded in the refined brand‐loyal scenario (considered the most relevant scenario) in all population groups except for infants at the mean and in all population groups at the 95th percentile.